Pharmacologic Management Of Acute Decompensated Heart Failure In The Emergency Department: A Systematic Review Of Clinical Outcomes (The Review of Diabetic Studies, 2025)
Background: Every year, there are over 650,000 visits to emergency departments in the United States due to acute decompensated heart failure, with high morbidity, mortality, and cost to the healthcare system. Although there have been improvements in caring for patients with chronic heart failure, the pharmacological management for patients with acute decompensated heart failure has demonstrated low efficacy for the mortality outcome in the emergency setting. The last several years have been highlighted by promising developments in their management. Though existing studies have demonstrated certain positive outcomes with various medications used in ADHF patients, their effects on patient outcomes, particularly hospital readmissions within the cardiogenic context, remain uncertain due to lack of direct research. This research aims to explore their use within the specified time framework.Methods: A systematic review of trials, registry data, and meta-analyses has been conducted, tracing the current studies on the use of ED-specific or early hospital pharmacologic therapy for ADHF published during the years 2015-2025. Included therapeutic groups involved loop diuretics, combination therapy, SGLT2 inhibitors, vasodilators, and new drugs. Information extraction involved outcomes, hemodynamics, and safety.Results: The current evidence suggests that the standard treatment for volume overload has been and still is treatment with loop diuretics. High-dose treatment and combination therapy with other agents have been proposed and gaining popularity. The other modality to enhance decongestion outcomes has been sequential nephron blockade with thiazides, SGLT2 inhibitors, and CARIS inhibitors. However, there has been conflicting evidence with regard to outcomes. The EMPULSE trial (2022) involving 530 patients has found early treatment with empagliflozin to be beneficial in clinical outcomes and quality of life parameters. The meta-analysis published in 2024 involving SGLT2 inhibitors in acute care (2,320 patients) has found decreased all-cause mortality (OR: 0.71) and hospitalization for heart failure (OR:0.73). The DICTATE-AHF trial (2024) involving 240 patients has found improved diuresis and natriuresis with treatment with dapagliflozin without detrimental effect on renal function. The use of natriuresis to guide diuretic treatment has been promising for decongestion. Combination treatment with other diuretics has also been found to be effective in increasing weight loss and decongestion parameters but has been found to be accompanied by increased serum creatinine.